Antibacterial activity of mango kernel extracts - Mirgahni , Mohamed Elwathig Saeed (2009)
This study is emphasized specifically on the potential of the mango “Mangifera Indica” seed kernel by discovering the prospective usage of mango seed kernels as a source of antibacterial compounds against Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli and Pseudomonas aeruginosa) bacterial strains. For this study, three types of mango were used; Blackgold, Lemak, and Waterlily from Malaysia and Thiland. The approach adopted for this purpose was by implementing agar well diffusion method. The results were expressed as the average diameter of bacterial inhibition zones surrounding the wells. The required solvents for the extraction were ethanol, methanol, acetone and phosphate buffer solutions were prepared in a different concentration; 0.10M, 0.05M, and 0.01M. The results showed that Lemak gave relatively high antibacterial activity among other types of mango ranging between 1.40 and 2.23 cm. For the known antibiotic, which was Tetracycline, under the same conditions the diameter of inhibition zones were between 2.30 to 3.30. Then, the minimum inhibition concentration tests were conducted for Lemak for two solvents extract that gave the highest inhibition zones which were methanol and acetone. The results showed that the minimum inhibition concentration of extracts that inhibited the growth of Escherichia coli and Bacillus subtilis was after 10X dilution (1 mM). The results obtained confirmed the antibacterial potential of mango kernels extracts and this would probably become an alternative source of new and natural antibacterial agents.